The paris spy eaudiobook - MacNeal, Susan Elia (Maggie Hope, 2017)
NEW YORK TIMES BESTSELLER • American-born spy and code-breaker extraordinaire Maggie Hope secretly navigates Nazi-occupied France to find two brave women during the darkest days of World War II in the latest novel in this bestselling series—“a treat for WWII buffs and mystery lovers alike” ( Booklist, on The Prime Minister’s Secret Agent ). Maggie Hope has come a long way since serving as a typist for Winston Churchill. Now she’s working undercover for the Special Operations Executive in the elegant but eerily silent city of Paris, where SS officers prowl the streets in their Mercedes and the Ritz is draped with swastika banners. Walking among the enemy is tense and terrifying, and even though she’s disguised in chic Chanel, Maggie can’t help longing for home. But her missions come first. Maggie’s half sister, Elise, has disappeared after being saved from a concentration camp, and Maggie is desperate to find her—that is, if Elise even wants to be found. Equally urgent, Churchill is planning the Allied invasion of France, and SOE agent Erica Calvert has been captured, the whereabouts of her vital research regarding Normandy unknown. Maggie must risk her life to penetrate powerful circles and employ all her talents for deception and spycraft to root out a traitor, find her sister, and locate the reports crucial to planning D-Day in a deadly game of wits with the Nazi intelligence elite. Praise for The Paris Spy “Engrossing . . . A fast-paced climax leads to an ending that will leave readers eagerly awaiting the next installment.” — Publishers Weekly “With its riveting plot and cliff-hanger finish, this is a solid addition to a series as well researched as it is entertaining.” — Booklist “You will grieve with Paris. You will be outraged by the destruction. You will be terrified for all the heroes, be there with them every step, and care desperately that they succeed and survive. And perhaps above all, like me, you will be overwhelmed with their sacrifice for the freedom we still enjoy.” —Anne Perry, New York Times bestselling author of the Charlotte and Thomas Pitt series and the William Monk series “This has to be Maggie Hope’s most exciting adventure yet. Vivid and fast-paced, crammed with authentic detail, The Paris Spy is an extraordinary trip through the edgy drama of wartime Paris, skillfully plotted and studded with cameos by real historical figures.” —Jane Thynne, author of the Clara Vine series